Exploratory studies of MTV Asia : a marketing cmmunications perspective. - Chan, Charmaine Pin Ping. (2008)
This study seeks to explore the (positive/negative)attitudes and perceptions of MTV Asia's target customer group in Singapore in relation to variables like its programming philosophy, marketing, brand name, image, veejays and content/presentation of it's programs. Results showed that young Singaporeans are generally neutral towards the MTV concept as opposed to the extreme feelings portrayed by the American counterparts.